2023
DOI: 10.2478/nispa-2023-0008
|View full text |Cite
|
Sign up to set email alerts
|

Blatant, not Latent: Patronage in Top-Level Appointments in Serbia

Abstract: This paper examines the model of party patronage in Serbia and its impact on the professionalisation of public administration. Drawing on case studies of the appointment and subsequent performance of heads of three prominent public organisations‐the National Bank of Serbia, the Anti‐Corruption Agency, and the Electro Industry of Serbia‐we demonstrate that, despite efforts to implement the Weberian principle of (neutral competence which involves the prevalence of meritocracy over partisan affiliation, patronage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Another important goal of the political appointments in key positions is to retain control over public institutions and public resources (Tomiċ and Pavloviċ, 2023), and therefore to influence the policy processes (Staroňová and Rybár, 2020). In countries with extensive politicization, politicization is used to reward loyal supporters and party members with jobs in public institutions (Kopecký et al, 2016).…”
Section: Goals Of Politicizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important goal of the political appointments in key positions is to retain control over public institutions and public resources (Tomiċ and Pavloviċ, 2023), and therefore to influence the policy processes (Staroňová and Rybár, 2020). In countries with extensive politicization, politicization is used to reward loyal supporters and party members with jobs in public institutions (Kopecký et al, 2016).…”
Section: Goals Of Politicizationsmentioning
confidence: 99%
“…The legacies of the relatively weak institutions of former communist countries provided the grounds for the emergence of political patronage of the recruitment in the civil service and of many policy domains (Kopecký and Spirova, 2011). Studies showed that even though former communist countries adopted reforms for civil service professionalization during the pre-accession to the European Union, politicization increased afterward and politicians found informal practices to appoint loyal subordinates, reward party clientele or extract public resources (Gajduschek and Staroňová, 2023;Tomiċ and Pavloviċ, 2023;Čehovin and Haček, 2015). These practices generated a movement back toward patronage (Peters and Bianchi, 2023;Staroňová and Rybár, 2020).…”
Section: Introductionmentioning
confidence: 99%